Advances in PET to assess pulmonary inflammation: A systematic review. Issue 130 (September 2020) - Vass, Laurence; Fisk, Marie; Lee, Sarah; Wilson, Frederick J.; Cheriyan, Joseph; Wilkinson, Ian
Highlights: This systematic review identifies the current status of PET to assess inflammatory lung disease and speculates on its future direction. Although FDG is the most widely used tracer, there are encouraging results in several more specific tracers. These PET tracers represent a powerful tool to aid the development of targeted therapies, diversify phenotypes and monitor progression. Abstract: Background: Respiratory diseases are one of the leading causes of death worldwide, yet effective treatment options remain limited. Although inflammation is thought to be a key driver in the pathogenesis and progression of several lung diseases, the underlying molecular mechanisms of lung dysfunction remain poorly understood. Imaging techniques may help to further our understanding of the pathophysiology and facilitate the translation of novel therapies. Positron Emission Tomography (PET) is a functional imaging technique which has the potential to interrogate the underlying inflammatory response. We present a systematic review of the literature summarising the emerging PET radiotracers developed to quantify pulmonary inflammation. Method: We performed a systematic review using the following databases: Medline, Embase, Scopus, PubMed, Web of Science and Cochrane. We included articles between 1995 and 2019 for all studies using PET radiotracers to evaluate inflammatory response in the lung. From a total of 911 articles covering both animal and human studies, two reviewers selected papers based on the inclusion/exclusion criteria and extracted data from 68 articles selected. Results: 53 out of 68 papers, including both human and animal studies, were eligible for synthesis. Heterogenous study populations and differences in study design, image acquisition and analysis made data pooling unfeasible; instead, we provide a narrative synthesis. Conclusions: Currently, very few novel radiotracers targeting lung inflammation have crossed the translational gap from animal models to human studies. Nevertheless, our results highlight a handful of promising tracers which warrant further evaluation in humans. 18 F-FDG has been investigated most extensively; although 18 F-FDG is not a specific inflammatory tracer, human studies of several pulmonary diseases support its use as a biomarker for inflammation. Despite ongoing debate about the optimal analysis methodology for 18 F-FDG lung images, standardisation of image acquisition and analysis should help to improve confidence in research outcomes. PET radiotracers can provide quantitative, targeted biomarkers which relate to the activity of molecular pathways and may expedite development of specific anti-inflammatory drugs.